Effect of hesperetin on interleukin-8 gene expression in MCF-7 cell line: Short Communication - Hamideh Dehghan; Milad Bideh; Mahboobeh Sabeti Akbar Abad; Fatemeh Zahra Biabani; Mohammed Zangooei (مجله دانشگاه علوم پزشکی بیرجند, 2023)
Breast cancer is recognized as the most common cause of cancer deaths in women. So far, no definite treatment has been identified there is no certain cure for breast cancer. The Ooverexpression of interleukin-8 is associated with increased tumor growth and breast cancer metastasis. Hesperetin is a flavonone sub-group of flavonoids that is abundantly found in citrus fruits, including lemons and oranges. Considering the anti-cancer and anti-inflammatory role of hesperetin, as also, well as the role of interleukin-8 in cancer metastasis and progression, in this studythe present study aimed to assess , the effect of hesperetin on the expression of the interleukin-8 gene in MCF-7 cell line has been investigated. The relative expression level of interleukin-8 gene in MCF-7 cell line at concentrations of 0, 25, 50, 100, and 200 µM hesperetin and durations of 6, 24, and 48 hours (with the concentration of 100 µM) was performed using the A real-time polymerase chain reaction (real-time PCR)Real-time method PCR was performed. The obtained Our results pointed out showed that the level of interleukin-8 gene expression decreases with an increase in by increasing the concentration of hesperetin (up to 100 µM), the level of interleukin-8 gene expression decreases. Furthermore, Also, the level of interleukin-8 gene expression in the 48-hour treatment was lower than that in the 24- and 6-hour treatments. Considering its various properties, including anti-cancer and anti-inflammatory properties, hesperetin could be effective in reducing the risk of metastasis and progression of breast cancer by reducing the expression of the interleukin-8 gene.